EFEK DEKOKTA DAUN PULUTAN (Urena lobata) TERHADAP FREKUENSI PERNAFASAN DAN GAMBARAN HISTOLOGI LAMELA INSANG IKAN ZEBRA (Danio rerio) FASE JUVENIL YANG DIPAPAR MALATHION SECARA KRONIK - Dluharrohimah Nur Imami; Ariani Ratri Dewi; Yudi Purnomo (Jurnal Kedokteran Komunitas, 2020)
Introduction: Malathion has an acetylcholinesterase inhibitor effect and increase free radicals resulting in damage to the structure and function of the respiratory organs. Urena lobata leaves decoction have antioxidant and anti-inflammatory potential controlled by the active substances quercetin and mangiferin. The study aims to prove the influence of Urena lobata leaves decoction to respiratory frequency and histological features of gills of juvenile Danio rerio chronically exposed by malathion.Method: Danio rerio age 45 days divided into 3 treatment groups and 2 control groups (n = 5). Malathion dose 2.5 mg/L administered to all groups except negative control for 40 days. Urena lobata leaves decoction was given to the treatment group at each dose 125 mg/L, 250 mg/L dan 500 mg/L. Respiratory frequency observed by recording and analyses using Windows Media Player software. Gills were colored with Hematoxylin Eosin and observed using a binocular microscopy with 1000x magnification. Data was analized using One Way ANOVA and Post Hoc LSD methods (p<0.05).Findings: Chronic expose of malathion in positive control group can increase respiratory rate and gills hyperplasia consecutively 25% and 90% compared to negative control (p<0.05). Administration of Urena lobata leaves decoction dose 125 mg/L and 250 mg/L inhibit increased respiratory rate about 10% and 20% consecutively compared to positive control (p<0.05). Urena lobata leaves decoction dose 125 mg/L, 250 mg/L and 500 mg/L inhibit secondary gills hyperplasia about 10%, 25% and 5% consecutively compared to positive control (p<0.05).Conclusion: Urena lobata leaves decoction was able to inhibit increasing respiratory rate and gills hyperplasia of juvenile Danio rerio chronically exposed by malathion.Keywords: Malathion, Urena lobata, Danio rerio, respiratory frequency, gills lamellae, chronic